Physiological and biochemical responses of wheat to synergistic effects of selenium nanoparticles and elevated CO2 conditions - Alsherif, Emad A.; Hajjar, Dina; Aldilami, Mohammad; AbdElgawad, Hamada (Frontiers in Plant Science, 2023)
The current study aimed to shed new light on the impacts of climate change on crops, one of which is the elevation of atmospheric CO2 (eCO2) levels. Accordingly, the attempts were to address how eCO2 shapes some metabolite content, antioxidant defense systems, and the components and functions of the photosynthetic cycle of the wheat (Triticum aestivum L.) plant; and to reveal if the application of selenium nanoparticles (SeNPs) can extend the biochemical and physiological shifts in eCO2-treated plants. With this goal, a pot experiment was carried out where the seeds were primed with SeNPs and plants were grown under two levels of CO2 concentrations (ambient CO2 (aCO2, 410 μmol CO2 mol−1; and eCO2 (710 μmol CO2 mol−1)). Although SeNPs+eCO2 treatment resulted in the highest accumulation of photosynthetic pigment content in leaves (+49-118% higher than control), strong evidence of the positive impacts on Rubisco activity (~+23%), and stomatal conductance (~+37%) was observed only under eCO2, which resulted in an improvement in photosynthesis capacity (+42%). When photosynthesis parameters were stimulated with eCO2, significant improvement in dry matter production was detected, in particular under SeNPs+eCO2 which was 7 times higher than control. The highest content of antioxidant enzymes, molecules, and metabolites was also recorded in SeNPs+eCO2, which might be associated with the nearly 50% increase in sodium content in shoots at the same treatment. Taken together, this is the first research documenting the effective synergistic impacts of eCO2 and SeNPs on the mentioned metabolites, antioxidants, and some photosynthetic parameters, an advantageous consequence that was not recorded in the individual application of these treatments, at least not as broadly as with the combined treatment.